Pressurized intraperitoneal aerosol chemotherapy with oxaliplatin in colorectal peritoneal metastasis. (April 2016) - Demtröder, C.; Solass, W.; Zieren, J.; Strumberg, D.; Giger‐Pabst, U.; Reymond, M.‐A.
Abstract: Aim: Pressurized intraperitoneal aerosol chemotherapy (PIPAC) is an experimental drug delivery method that applies chemotherapy into the abdominal cavity as an aerosol under pressure. We present the first results obtained with PIPAC in colorectal peritoneal metastasis (CPM). Method: This is a retrospective analysis. PIPAC was applied in 17 consecutive patients with pretreated CPM. All patients had previously undergone surgery, and 16 had undergone previous lines of systemic chemotherapy (median, two lines). The mean peritoneal metastasis index (peritoneal cancer index) was 16 ± 10. Forty‐eight applications of PIPAC with oxaliplatin (92 mg/m 2 ) were given every 6 weeks at 37°C and 12 mmHg for 30 min. The outcome criteria were microscopic pathological response, survival and adverse events according to Common Terminology Criteria for Adverse Events (CTCAE) version 4.0. Results: Forty‐eight PIPAC administrations were performed with no intra‐operative complications. The mean number of PIPAC administrations per patient was 2.8 (minimum one, maximum six). Postoperative adverse events (CTCAE level 3) were observed in four patients (23%), no CTCAE level‐4 adverse events were reported. The hospital mortality was zero. Objective tumour responses were observed in 12/17 patients (71%), and the overall responses were as follows: complete pathological response (seven patients), major response (four patients), partial response (one patient), no response (two patients) and not eligible (three patients). The mean survival after first PIPAC was 15.7 months. Conclusion: Repeated PIPAC with oxaliplatin can induce the regression of pretreated CPM. The toxicity appears to be low. These preliminary results are encouraging and justify prospective clinical studies.